Visual perseveration in temporal lobe epilepsy. Issue 6 (June 1979) - Swash, M
Abstract : Ictal visual perseveration is reported in two patients with temporal lobe epilepsy. A distinction is drawn between visual perseveration and palinopsia, or recurrence of a visual image.